The Relationship between a Language and Culture - Muborak Sagatova (International Journal on Integrated Education, 2022)
Teaching culture should be an essential part of teaching English as a foreign language because one of the main aims of teaching a foreign language is intercultural communicative competence (ICC). The aim of this article is to explore the relationship between language and culture and to determine to what extent culture is incorporated into the curriculum of schools.